Association of Side-Branch Treatment and Patient Factors in Left Anterior Descending Artery True Bifurcation Lesions: Analysis from the GRAND-DES Pooled Registry. (28th December 2020) - Oh, Gyu Chul; Park, Kyung Woo; Kang, Jeehoon; Han, Jung-Kyu; Yang, Han-Mo; Kang, Hyun-Jae; Koo, Bon Kwon; Kim, Hyo-Soo
Abstract : Background and Objectives . In most bifurcation lesions, keeping the procedure simple by not treating the side-branch (SB) lesion when possible is considered the best method. However, because of improvements with 2 nd generation drug-eluting stents (DESs), it remains unknown whether treatment of the SB may improve outcomes in certain subgroups, especially when exclusively using 2 nd generation DESs. We report the outcome of SB treatment in a group of patients exclusively receiving newer generation DES for bifurcation PCI. Methods . Patients undergoing PCI to left anterior descending (LAD) bifurcation lesions with contemporary DES were analyzed from a nationwide registry. Baseline risk was assessed using the Age, Creatinine, and Ejection Fraction (ACEF) score. Target lesion failure (TLF), a composite of cardiac death, target vessel myocardial infarction, and target lesion revascularization, was assessed at 3 years. Results . Among 1, 089 patients with LAD bifurcation lesions, 548 (50.3%) patients underwent SB treatment. The SB treatment group showed a nonsignificant, but numerically lower rate of 3-year TLF (6.6% vs. 9.2%, HR 0.75, 95%CI 0.44–1.28, p  = 0.29). In patients with low pretreatment risk (ACEF<1.22), SB treatment was associated with a lower rate of 3-year TLF (HR 0.43, 95%CI 0.19–0.96, p  = 0.04), while no significant difference was observed in patients with high risk (ACEF≥1.22). The difference in the low risk group was mostly driven by target lesion revascularization (HR 0.24, 95%CI 0.08–0.75, p  = 0.01). Conclusions . SB treatment for LAD bifurcation lesions showed favorable long-term outcomes compared with main-branch-only intervention, especially in patients with low pretreatment risk.